PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM DENGAN SUKU BUNGA BANK SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA (Periode tahun 2017-2021) - Kharismiati; Riana Susanti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research aims to determine the effect of financial ratios on stock returns and to determine the effect of interest rates in moderating the relationship between financial ratios and stock returns in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2022 period. The data used are financial reports published in 2017 – 2021. This research is a comparative clausal research, which analyzes the causal relationship between two or more variables. The variables used in this study are several fundamental factors of financial ratios namely X1 Current Ratio (CR), X2 Total Asset Turnover (TATO), X3 Debt of Equity (DER), and X4 Return on Investment (ROI) as independent variables and Y stock returns as the dependent variable with Z Bank interest rates as the moderating variable. The objects of research are 30 companies engaged in the property and real estate sector that publish financial reports on the Indonesia Stock Exchange (IDX) from 2017 to 2021. These financial reports provide complete information about the company, where in the financial statements the stakeholders make as a basis for consideration of decision making. Based on purposive sampling, 30 property and real estate companies were obtained for the 5 year period from 2017-2021. The data processing method used in this research is a causality test with regression analysis and moderate regression analysis using SPSS version 26. The results of this study indicate that the current ratio (CR) has a significant positive effect on stock returns, total asset turnover (TATO) has a significant negative effect on stock returns, the debt to equity ratio (DER) has a significant positive effect on stock returns, return on investment (ROI). has a significant positive effect on stock returns and bank interest rates does not strengthen the relationship between the current ratio (CR), total asset turnover (TATO), return on investment (ROI) and stock returns. Bank interest rates strengthen the relationship between the debt to equity ratio (DER) and stock returns.